Beyond weight loss: exploring the neurological ramifications of altered gut microbiota post-bariatric surgery - Rashed T. Almheiri; Baraa Hajjar; Saif M. I. Alkhaaldi; Nadia Rabeh; Sara Aljoudi; Khaled S. Abd-Elrahman; Hamdan Hamdan (Journal of Translational Medicine)
Abstract This review discusses findings related to neurological disorders, gut microbiota, and bariatric surgery, focusing on neurotransmitters, neuroendocrine, the pathophysiology of bacteria contributing to disorders, and possible therapeutic interventions. Research on neurotransmitters suggests that their levels are heavily influenced by gut microbiota, which may link them to neurological disorders such as Alzheimer's disease, Parkinson's disease, Multiple sclerosis, Depression, and Autism spectrum disorder. The pathophysiology of bacteria that reach and influence the central nervous system has been documented. Trends in microbiota are often observed in specific neurological disorders, with a prominence of pro-inflammatory bacteria and a reduction in anti-inflammatory types. Furthermore, bariatric surgery has been shown to alter microbiota profiles similar to those observed in neurological disorders. Therapeutic interventions, including fecal microbiota transplants and probiotics, have shown potential to alleviate neurological symptoms. We suggest a framework for future studies that integrates knowledge from diverse research areas, employs rigorous methodologies, and includes long-trial clinical control groups.